Dissecting the novel abilities of aripiprazole: The generation of anti-colorectal cancer effects by targeting Gαq via HTR2B - Haowei Liu; Qiuming Huang; Yunqi Fan; Bo Li; Xuemei Liu; Changhua Hu (Elsevier, 2023)
Colorectal cancer (CRC) is a type of malignant tumor that seriously threatens human health and life, and its treatment has always been a difficulty and hotspot in research. Herein, this study for the first time reports that antipsychotic aripiprazole (Ari) against the proliferation of CRC cells both in vitro and in vivo, but with less damage in normal colon cells. Mechanistically, the results showed that 5-hydroxytryptamine 2B receptor (HTR2B) and its coupling protein G protein subunit alpha q (Gαq) were highly distributed in CRC cells. Ari had a strong affinity with HTR2B and inhibited HTR2B downstream signaling. Blockade of HTR2B signaling suppressed the growth of CRC cells, but HTR2B was not found to have independent anticancer activity. Interestingly, the binding of Gαq to HTR2B was decreased after Ari treatment. Knockdown of Gαq not only restricted CRC cell growth, but also directly affected the anti-CRC efficacy of Ari. Moreover, an interaction between Ari and Gαq was found in that the mutation at amino acid 190 of Gαq reduced the efficacy of Ari. Thus, these results confirm that Gαq coupled to HTR2B was a potential target of Ari in mediating CRC proliferation. Collectively, this study provides a novel effective strategy for CRC therapy and favorable evidence for promoting Ari as an anticancer agent.